Organisation structure and enterprise modelling in ERP realisation. (1st January 2002) - Ip, Wai-Hung; Chen, Bocheng
In the paper, the authors investigate the organisation structure in an ERP system. Using SAP R/3 as an example, it identifies that the structure should be established following its functional needs. Each ERP function module should have its own organisation structure, and each function module should have its own power control structure, all of them being constituent with the "virtual" enterprise. Moreover, the authors propose the use of Enterprise Modelling to analyse the gap and map between enterprise organisation structure and the virtual enterprise in system design and implementation. Various examples of this modelling process using IDEF are given. Finally, we observe that Enterprise Modelling provides the essential tools and methods necessary for Business Process Reengineering and Continuous Improvement as well as for customising ERP software and avoiding the complete rebuilding of the whole enterprise structure. This provides the flexibility and scalability to change organisation structure only in the "virtual" elements.